2010
DOI: 10.1242/dev.041913
|View full text |Cite
|
Sign up to set email alerts
|

Crumbs is required to achieve proper organ size control duringDrosophilahead development

Abstract: SUMMARYCrumbs (Crb) is a conserved apical polarity determinant required for zonula adherens specification and remodelling during Drosophila development. Interestingly, crb function in maintaining apicobasal polarity appears largely dispensable in primary epithelia such as the imaginal discs. Here, we show that crb function is not required for maintaining epithelial integrity during the morphogenesis of the Drosophila head and eye. However, although crb mutant heads are properly developed, they are also signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 78 publications
(110 reference statements)
8
75
1
1
Order By: Relevance
“…Herranz et al (2006) concluded that in larval wing discs absence of Crb enhances intramembrane proteolytic processing of Notch by γ-secretase, called S3 cleavage, which depends on ligand-induced S2 cleavage (Mumm et al, 2000) and is followed by the translocation of the intracellular portion of Notch into the nucleus and activation of downstream genes. Along the same line, Richardson and Pichaud (2010) proposed, based on inhibition experiments, that absence of Crb in eye imaginal discs enhances Dl-mediated, metalloproteasedependent S2 cleavage of Notch, and showed increased internalised Notch in uptake assays in the absence of Crb. Our results differ from those previously published in that: (1) in pupal wings, endocytosis of Notch in the absence of crb does not depend on the ligands Dl and Ser nor on Psn, suggesting that it is independent of the S2 and S3 cleavage of Notch; and (2) endocytosis of Notch in crb mutant pupal cells activates the dx-dependent ligand-independent Notch pathway.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Herranz et al (2006) concluded that in larval wing discs absence of Crb enhances intramembrane proteolytic processing of Notch by γ-secretase, called S3 cleavage, which depends on ligand-induced S2 cleavage (Mumm et al, 2000) and is followed by the translocation of the intracellular portion of Notch into the nucleus and activation of downstream genes. Along the same line, Richardson and Pichaud (2010) proposed, based on inhibition experiments, that absence of Crb in eye imaginal discs enhances Dl-mediated, metalloproteasedependent S2 cleavage of Notch, and showed increased internalised Notch in uptake assays in the absence of Crb. Our results differ from those previously published in that: (1) in pupal wings, endocytosis of Notch in the absence of crb does not depend on the ligands Dl and Ser nor on Psn, suggesting that it is independent of the S2 and S3 cleavage of Notch; and (2) endocytosis of Notch in crb mutant pupal cells activates the dx-dependent ligand-independent Notch pathway.…”
Section: Discussionmentioning
confidence: 85%
“…It has been proposed that in Drosophila eye discs the absence of Crb facilitates incorporation of Notch into early endocytic vesicles marked by Hrs (Richardson and Pichaud, 2010). Therefore, we asked whether increased Notch endocytosis in crb mutant cells observed in pupal wings depends on the Notch ligands Delta (Dl) and Serrate (Ser).…”
Section: Crb Negatively Regulates Notch Activity Via Its Extracellulamentioning
confidence: 97%
See 2 more Smart Citations
“…This activation of Notch signaling is correlated with an increased endocytosis of Notch and its ligand Delta. Hence, independent of its function in cell polarity, Crb acts as an inhibitory factor to Notch activation by limiting endocytosis (Richardson and Pichaud, 2010). Crb is also involved in the inhibition of Notch signaling in vertebrates like zebrafish, in which Notch activity is necessary for the apical mitosis of neuroepithelial cells during embryogenesis (Ohata et al, 2011).…”
Section: Introductionmentioning
confidence: 99%